An Integrated Approach of Using Polystyrene Foam as an Attachment System for Growth of Mixed Culture of Cyanobacteria with Concomitant Treatment of Copper Mine Waste Water. (31st December 2013) - Chaturvedi, Venkatesh; Chandravanshi, Monika; Rahangdale, Manoj; Verma, Pradeep
Abstract : Cyanobacteria have tremendous applications in areas such as production of biofuels and pharmaceutically important pigments and are used as an adsorbent for the removal of toxic metabolites. However, large scale production of Cyanobacteria is not economically feasible due to high cost involved in separation of biomass. In this context, different attachment systems have been developed for the growth of Cyanobacteria on a solid support. In this study, a simple and economical attachment system using polystyrene foam for growth of Cyanobacteria has been presented. Results clearly indicate that high biomass yield can be obtained in attached system when compared to suspended system. In attachment system, the biomass yield showed 21.4%, total protein content showed 29.2%, chlorophyll content showed 11.1%, and carotenoid content showed 13.1% increase as compared to the suspended system. The attachment system can also support the growth of Cyanobacteria in presence of copper mine waste water with concomitant removal of copper ions. These results were corroborated by COD analysis, which indicated significant reduction. Further, copper removal was high in attached system as compared to suspended system. It appears that attachment system offers protection for growing Cyanobacteria and can be effectively employed for growing Cyanobacteria in presence of waste water coming from different sources.